Bio-resource Utilization and Socio-economic Conditions of the People Living in Ithing and Karang Island Villages of Loktak Lake, Manipur, India - Laishram, Jogesh; Dey, Mithra (International Journal of Bio-resource and Stress Management, 2023)
Bio-resources from the wetlands form the major economy of the rural people living in and around it. There is need to conserve the valuable resources of the wetlands from various anthropogenic pressures so that livelihoods of the people are secured. The main aim of the present study was to investigate the natural resource dependency of the people living in Ithing and Karang, the two island villages of Loktak Lake and assess the socio-economic conditions of the villages. Questionnaire survey and direct observation were used for collection of data. Randomly selected households were administered with the questionnaire to obtain information on the various types of bio-resources utilized by them and to find out the socio-economic conditions of the households. It was found that among the bio-resources used from the lake, fishes and prawns (100% and 68.66%) were the major resources. Water from the lake is used for drinking (100%) and firewood (Phragmites karka, Saccharum munja, etc.) was collected from lake and used (47.33%) as fuel. Fishing and handloom are the major occupations. Average size of family is 8.12 and 31.71% have Primary (Nursery-VIII) level education which is highest in terms of educational level. 54.66% of the respondents were found to have total annual income in the range of Rs. 60,001-90,000/-. Majority of the respondents were found to have own land but lived in kuccha houses (65.33%) and used open pit toilets (46.66%). All the 40 respondents felt that the natural resources of Loktak Lake is declining. Therefore, for the conservation and sustainable development of the lake effective conservation and management programmes need to be taken up by the government, local authorities and communities jointly. Traditional fishing with Athaphums, prevalent earlier has now been stopped by Loktak Development Authority as a conservation measure. Community awareness and participation is essential for successful and sustainable managements.